The Effectiveness of telemedicine approach as a treatment to reduce severity of temporomandibular disorders - Ricca Chairunnisa; Siti Dyah Fadilla (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Temporomandibular disorder (TMD) is the most common pain in the maxillofacial area. Overall prevalence of TMD was approximately 31% for adults/elderly and 11% for children/adolescents. TMD is considered a multifactorial disorder. There are various treatments for TMD, one of which is jaw exercises therapy which is the most widely used initial treatment to relieve signs and symptoms. Currently, conventional therapy for TMD patients has been difficult to control patient compliance. Hence, this therapy can be done at home independently through telemedicine as an alternative tool to rehabilitateate the patients that can be accessed via smartphone. Purpose: To determine the severity of TMD before and after jaw exercises and the effect of telemedicine approach using jaw exercises via smartphone apps on dental students. Methods: This study used a quasi-experimental method with a one-group pretest post-test design using Fonseca anamnestic index (FAI) questionnaire to measure the severity before and after two weeks of jaw exercises on 35 dental students using purposive sampling based on inclusion and exclusion criteria. Wilcoxon signed-rank test was used to analyze the data (p<0.05). Results: Before jaw exercises, 21 people (60%) had mild TMD, 14 people (40%) had moderate TMD, and none had severe TMD. After jaw exercises, the severity of 9 people (42.8%) in the mild TMD group has decreased (p=0.007), and the severity of 11 people (78.5%) in the moderate TMD group has decreased (p=0.003). Conclusion: There was positive effect that decreased the level of severity of TMD through telemedicine approach after jaw exercises via smartphone apps on dental students.